Statistical Analysis of High–Energy Particle Perturbations in the Radiation Belts Related to Strong Earthquakes Based on the CSES Observations - Lu Wang; Zhenxia Zhang; Zeren Zhima; Xuhui Shen; Wei Chu; Rui Yan; Feng Guo; Na Zhou; Huaran Chen; Daihui Wei (Remote Sensing, 2023)
Earthquakes (EQs) are a significant natural threat to humanity. In recent years, with advancements in space observation technology, it has been put forward that the electromagnetic effects of earthquakes can propagate into space in various ways, causing electromagnetic radiation and plasma disturbances in space and leading to high–energy particle precipitation. The China Seismo-Electromagnetic Satellite (CSES) is specifically designed for monitoring the space electromagnetic environment. In our study, we select 78 strong earthquakes from September 2018 to February 2023 (global earthquakes with M ⩾ 7.0 and the major seismic regions in China with M ⩾ 6.0). We focus on <semantics>10∘</semantics> of the latitude and longitude around the epicenter, spanning from 15 days before the earthquake to 5 days after, and look for anomalies in spatial evolution and temporal evolution. We present some typical cases of electron flux perturbation and summarize the anomalies of all 78 cases to look for regularity in EQ–related particle anomalies. Notably, we introduce two cases of simultaneous electromagnetic and energetic particle anomalies during earthquakes. And we propose a conjecture that the particle precipitation may be the result of wave–particle interactions triggered by seismic activity.